PENGEMBANGAN BAHAN AJAR BAHASA INDONESIA BERBASIS STEAM MENGGUNAKAN APLIKASI FLIPBOOK - Wikanengsih, Wikanengsih; Rostikawati, Yeni (Jurnal Semantik, 2024)
The development of learning materials is a demand that is needed in the future, especially the application of hybrid learning. The use of hybrid learning materials is very urgent to anticipate the situation, both offline learning, computer-based learning, and online learning. This research aims to develop a STEAM-based teaching material model with a Flipbook application for Indonesian Language subjects in class X of high school. The method used is research and development (R&D) with data collection techniques through observation, questionnaires, and validation. Descriptive-qualitative analysis was applied, and the test results showed an average increase of 0.567 (medium category). The average difference between the initial test and the final test was 23.8, which indicates that this STEAM-based teaching material is effective for use at the high school level.